ANALISIS PENGARUH VARIANS ANGGARAN PENJUALAN DAN ANGGARAN BIAYA PENJUALAN TERHADAP LAPORAN LABA RUGI. STUDI PADA PT COMBIPHAR PERIODE 2012 – 2014 - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA; Watini Watini (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2016)
This Paper aims to analyze impact of sales and sales cost budget variance to Income Statement in PT Combiphar in 2012 – 2014. This paper analyzed quantitevely by Regression analysis. Data collected from PT Combiphar are sales budget, sales cost budget and Income Statement. Result of this study show that Income Statement impacted significantly by variance sales and sales cost budget in partial test, and by simultaneously both of variance sales and sales cost budget impact significantly to Income Statement in 57.6%.